1991
DOI: 10.1159/000247806
|View full text |Cite
|
Sign up to set email alerts
|

Loose Anagen Hair in a Child with Noonan’s Syndrome

Abstract: We report on a 4½-year-old girl affected by loose anagen hair and Noonan’s syndrome. The girl had short, blond, easily pluckable hair that had never been cut. The trichogram showed an absolute prevalence of abnormally shaped anagen bulbs lacking inner and outer root sheaths. A scalp biopsy evidenced a marked cleft formation between fragmented inner root sheaths and irregularly shaped hair shafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…25,26 The pathogenesis of loose anagen hair remains unknown. A scalp biopsy in a patient with loose anagen hair showed marked cleft formation between the inner root and the irregularly shaped hair shafts.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 The pathogenesis of loose anagen hair remains unknown. A scalp biopsy in a patient with loose anagen hair showed marked cleft formation between the inner root and the irregularly shaped hair shafts.…”
Section: Discussionmentioning
confidence: 99%
“…More than one keratin gene may be involved in the pathogenesis of LAS. 306 There is evidence of autosomal dominant transmission with variable expression and incomplete penetrance, 304,306,307 but sporadic cases and rare associations [308][309][310] have been reported.…”
Section: Uncombable Hair Syndromementioning
confidence: 99%
“…4,5,[8][9][10][11][12][13][14][15][16][17][18][19]21,22 Parents may also be worried by the patients' diffuse hair loss or localized patches of alopecia. 4,5,[8][9][10][11][12][13][14][15][16]19,22,23 They may have easily pluckable hair, although this sign is not always obvious. 9,10,[12][13][14][15]19,21,23 However, as in our series, the pull test result is usually positive, with more than 50% of dystrophic anagen hairs per pull in pediatric cases of LAHS.…”
Section: Commentmentioning
confidence: 99%
“…Based on molecular studies, a dominant inheritance of LAHS was confirmed in the 3 families in whom * References 4,9,10,[12][13][14]16,18,19,[21][22][23]. the mutation was found, because both children and fathers bore the mutation.…”
Section: Commentmentioning
confidence: 99%